Triboelectric Nanogenerators: Ion‐Enhanced Field Emission Triboelectric Nanogenerator (Adv. Energy Mater. 37/2019). Issue 37 (4th October 2019) - Chung, Jihoon; Heo, Deokjae; Shin, Gunsub; Choi, Dukhyun; Choi, Kyungwho; Kim, Dongseob; Lee, Sangmin
Abstract : In article number1901731, Dongseob Kim, Sangmin Lee and co‐workers report a new triboelectric nanogenerator (TENG) mechanism utilizing ion‐enhanced field emission (IEFE). Using a simple IEFE layer, electrons can flow directly in between two electrodes and as a consequence the root mean square power of the IEFE TENG is 635% higher than a conventional TENG.